IMITATIONS OF THE ANTI-RACIST EDUCATIONAL POLICY IMPLEMENTED BY THE ETHNIC-RACIAL DIVISION OF THE MUNICIPAL EDUCATION-AP (Práxis Educativa, 2022)
This article contextualizes the applicability of anti-racism legislation in schools, through the Ethnic-racial Division of the Municipal Education Secretariat (SEMED), Macapá, Amapá which has the institutional function of preparing the institution itself, as well as schools, staff, teachers and students for the fulfillment and promotion of educational policies that guarantee the right to public education for the black population and historically excluded groups. The methodology used was qualitative research and, for data collection, we used the semi-structured interview with the director of the above division. The study revealed that prejudiced and racist beliefs and mentalities collaborate so that, within the scope of municipal public management, Law 10.639/ 03 is not enforced in / by schools in the Municipality of Macapá.